P. 1
Z Transform - control

# Z Transform - control

4.5

|Views: 873|Likes:

See more
See less

05/11/2014

pdf

text

original

# EE452 Digital Control Dr.

Salah Foda Page 1

The Z-Transform

Sampled Data
The generalized function o(t) (also known as the impulse function) is useful in the definition
and analysis of sampled-data signals. Figure 1 below shows a simplified graph of an impulse.

Figure 1: Simplified graph of an impulse function

For an impulse, it can be shown that
) f(t dt ) t δ(t f(t)
0 0
= ÷
í
·
· ÷

(1)
This property is called the sifting property and may be used to define a sampled signal f
*
(t) as
shown in Figure 2 below. The sampled signal is basically f(t) modulated by the pulse train
p(t) given by
p(t) =
¯
·
÷· =
÷
n
nT) δ(t
(2)

Figure 2: Ideal impulse sampling

Therefore
f
*
(t) = f(t) p(t) =
¯
·
÷· =
÷
n
nT) δ(t f(nT)
(3)
So that the sampled signal is an amplitude modulated train of pulses. If each pulse is replaced
with the number f(nT), it is then called discrete-time signal. Finally, if f(t) is defined only
over t > 0, the summation in Eq. (3) is taken over [0,·].
o(t-t
0
)
t
0

t
t
p(t)
t
f(t)
t
f
*
(t)
EE452 Digital Control Dr. Salah Foda Page 2

The z-Domain
The Laplace and z-transforms are closely related techniques. To demonstrate this, we will
start with the Laplace transform and show how it can be changed into the z-transform. The
single-sided Laplace transform of the time domain f(t) is defined as:
í
·
÷
=
0
f(t) F(s) dt e
st

(4)
where F(s) is the s-domain representation of the signal f(t). The above equation analyzes the
time domain signal in terms of sine and cosine waves that have an exponentially changing
amplitudes. This can be understood by using the substitution s = o+je so that the Laplace
transform becomes:
í
·
÷ ÷
=
0
} {f(t) ) , F( dt e e
t j t e o
e o

(5)

Figure 3: An interpretation of F(o,) for a unit step u(t)
Now, take the Laplace transform of the sampled-data signal f
*
(t) given by Eq. (3)
dt e dt e
st
n
st ÷
·
·
=
·
÷
í
¯
í
÷ = =
0
0
0
* *
nT) δ(t f(nT) (t) f (s) F

= =
÷
·
=
¯
nTs
n
e
0
f(nT) f(0) + f(T) e
-sT
+ f(2T) e
-2sT
+ f(3T) e
-3sT
+ 

(6)
This equation is our starting point to define the z-transform of a sampled signal. It also relates
in a direct way the s-transform and the z-transform as will be soon illustrated. Define the
forward delay operator z = e
sT
and rewrite Eq. (6) as follows:
F(z) = =
÷
·
=
¯
n
n
z
0
f(nT) f(0) + f(T) z
-1
+ f(2T) z
-2
+ f(3T) z
-3
+  (7)
where F(z) is called the z-transform of the discrete signal f(nT) or Z{f(t)}.
EE452 Digital Control Dr. Salah Foda Page 3

Example: Find the z-transform for the unit step u(t)=1 for t ≥ 0 and is zero for negative time.
SOLUTION: Substitute for u(t) in Eq. (7) to get
U(z) = =
÷
·
=
¯
n
n
z
0
u(nT) 1+ z
-1
+ z
-2
+ z
-3
+  =
1
1
1
÷
÷ z
=
1 ÷ z
z
given that |z| >1.

Properties of the z-transform:
(1) Linearity: Given f(t) and g(t) with corresponding F(z) and G(z), then for arbitrary
constants α, βeIɌ or ₵
Z{α f(t)+ β g(t)}= αF(z)+ βG(z)
(8)
(2) Translation: For m > 0
Z{f(nT+mT)}= z
m
F(z) ÷ z
m
f
0
÷ z
m-1
f
1
÷  ÷ zf
m-1
(9)
and Z{f(nT÷mT)}= z
÷m
F(z) (10)
PROOF:
Z{f(nT+mT)}=
n
n
z
÷
·
=
¯
+
0
mT) f(nT = z
m
) (
0
mT) f(nT
m n
n
z
+ ÷
·
=
¯
+
= z
m
 + +
+ ÷
+
÷
·
=
¯
) 1 (
1 m
0
m
f f
m m
n
z z = z
m
F(z) ÷ z
m
f
0
÷ z
m÷1
f
1
÷  ÷z f
m-1

Proof for the second case is similar except that f(nT) is assumed zero for negative indices.

(3) Complex Differentiation:
Z {nT f(nT)}= ÷Tz dF(z)/dz
(11)
PROOF: Note that dF(z)/dz = ÷ f
1
z
÷2
÷ 2f
2
z
÷3
÷3f
2
z
÷4
÷ 

Example: Find the z-transform for the ramp function r(t) = t for t ≥ 0.

SOLUTION: Using complex differentiation property
R(z) = ÷zT dU(z)/dz = ÷zT d(
1 ÷ z
z
)/dz = ÷zT
2
) 1 (
1
÷
÷
z
=
2
) 1 ( ÷ z
Tz

(4) Frequency Scaling: Z{o
n
f(nT)}=F(o
÷1
z) (12)

PROOF: Using translation property
Z{o
n
f(nT)}=
n
n
z
÷ ÷
·
=
¯
) ( f
1
0
n
o = F(o
÷1
z)
EE452 Digital Control Dr. Salah Foda Page 4

(5) Initial Value Theorem: f(0) =
· ÷ z
lim F(z) (13)
(6) Final Value Theorem: f(·) =
1
lim
÷ z
(z÷1)F(z) (14)
PROOF: Using translation property
Z {f
n+1
÷f
n
}=
· ÷ N
lim
n
N
n
z -
÷
=
+ ¯
) f (f
0
n 1 n = z F(z) ÷ z f(0) ÷ F(z)

Now, let z =1 and observe that
1
lim
÷ z
(z÷1) F(z) ÷ f(0) =
÷· N
lim {(f
1
÷f
0
)+ (f
2
÷f
1
)+ +(f
N
÷f
N-1
)} = f(·) ÷ f(0).
Note that this final value exists only if (z-1)F(z) has its poles within unit circle.

The following table summarizes the Laplace and z-transforms for a few of the standard
functions.

Table: Standard Laplace and z-transforms
Time Function f(t) t >0 Laplace Transform F(s) z-transform F(z)

Kronecker delta o(t) 1 1
Step function u(t)
s
1

1 ÷ z
z

Power function a
t

a z
z
÷

Ramp t
2
1
s

2
) 1 ( ÷ z
Tz

Parabolic function t
2

3
2
s

3
) 1 (
) 1 (
÷
+
z
z z T

t
k

1
!
+ k
s
k

] [ ) 1 ( lim
0
T k
k
k
ze
z
o
o o
÷
÷ c
c
÷

e
÷at

a s +
1

aT
e z
z
÷
÷

te
÷at

2
) (
1
a s +

2
) (
aT
aT
e z
Tze
÷
÷
÷

1÷e
÷at

) ( a s s
a
+

) ( ) 1 (
) 1 (
aT
aT
e z z
e z
÷
÷
÷ ÷
÷

Damped sine
e
÷at
sin(et)
2 2
) ( e
e
+ + a s

aT aT
aT
e T ze z
T ze
2 2
cos 2
sin
÷ ÷
÷
+ ÷ e
e

Damped Cosine
e
÷at
cos(et)
2 2
) ( e + +
+
a s
a s

aT aT
aT
e T ze z
T ze z
2 2
2
cos 2
cos
÷ ÷
÷
+ ÷
÷
e
e

EE452 Digital Control Dr. Salah Foda Page 5

The Inverse z-transform
There are several methods to obtain the inverse of the z-transforms. We shall discuss two
simple methods; long division and partial fraction expansion. Both are illustrated though the
following examples.

Example: Find the inverse z-transform for
F(z) =
) 1 ( ) 5 . 0 (
2 . 0
÷ +
+
z z
z

SOLUTION:

(a) Using long division

z
÷1
+0.7z
÷2
+ 0.85 z
÷3
+0.775 z
÷4
+ 
z
2
÷0.5z ÷0.5
z+0.2

z ÷0.5÷0.50 z
÷1

0.7+0.50 z
÷1

0.7÷0.35 z
÷1
÷0.35 z
÷2

0.85 z
÷1
+0.35 z
÷2

0.85 z
÷1
÷0.425 z
÷2
÷0.425 z
÷3

0.775 z
÷2
+0.425 z
÷3

Or, simply
F(z) =
n
n
z
÷
·
=
¯
0
f(nT) = z
÷1
+0.7z
÷2
+ 0.85 z
÷3
+0.775 z
÷4
+ 
(b) Using partial fractions
F(z) can be expanded as F(z) =
) 1 (
8 . 0
) 5 . 0 (
2 . 0
÷
+
+ z z
so that

z F(z) =
) 1 (
8 . 0
) 5 . 0 (
2 . 0
÷
+
+ z
z
z
z

and from z-transform table, we get f
n+1
= 0.2(÷0.5)
n
+ 0.8 for n > 0
and f
0
=
· ÷ z
lim
) 1 ( ) 5 . 0 (
2 . 0
÷ +
+
z z
z
= 0 as confirmed in (a).

(c) Computation using Matlab
The following Matlab code may be used to confirm the above results:
>> delta=[1 zeros(1,15)];
>> num=[0 1 0.2];
>> den=conv([1 .5],[1 -1]);
>> f=filter(num,den,delta)
f = 0 1 0.7 0.85 0.775 0.8125 0.7937 0.8031 0.7984 0.8008
0.7996 .8002 0.7999 0.8 0.8 0.8

Note that the sequence f
n
is seen as the impulse response of a filter with F(z) as its
transfer function.
EE452 Digital Control Dr. Salah Foda Page 6

Example: Find the inverse z-transform for
F(z) =
) 6 5 (
2
+ ÷ z z
z

SOLUTION:
(a) Using long division
F(z) =
n
n
z
÷
·
=
¯
0
f(nT) = z
÷1
+5z
÷2
+ 19 z
÷3
+ 65 z
÷4
+ 
Also, F(z)/z can be expanded as F(z)/z =
) 6 5 (
1
2
+ ÷ z z
=
) 2 (
1
) 3 (
1
÷
÷
÷ z z

Hence F(z) =
) 2 ( ) 3 ( ÷
÷
÷ z
z
z
z

So that f((nT) = (3)
n

÷ (2)
n
, for n > 0.

(b) Using Matlab:

>> delta=[1 zeros(1,5)];
>> num=[0 1 0];
>> den=[1 -5 6]);
>> f=filter(num,den,delta)
f = 0 1 5 19 65 211

(c) Using Symbolic Toolbox:

>> syms f F n z
>> F=z/(z^2-5*z+6);
>> f=iztrans(F)
f = -2^n+3^n

Example: Find the value of the infinite series
f =
k
k
) 5 . 0 ( k
0
¯
·
=

SOLUTION: First, we may note that f is simply F(z) evaluated at z =1 (provided that
F(z) has no poles outside the unit circle). Let us evaluate F(z) as the complex
differentiation of
5 . 0 ÷ z
z
i.e. F(z) = ÷z
)
5 . 0
(
÷ z
z
dz
d
=
2
) 5 . 0 (
2
÷ z
z

Hence, the sum f = F(1) = 8.

Example: Using z-transform table and partial fraction expansion, find the inverse z-
transform for
F(z) =
) 1 ( ) 1 (
) 1 (
2
÷ + ÷
+
z z z
z z

SOLUTION: First, let us expand F(z) using partial fractions in the form
F(z)/z =
) 1 ( ) 1 (
) 1 (
2
÷ + ÷
+
z z z
z
=
) 1 (
) 1 (
2
+ ÷
+
+
÷
z z
c z b
z
a
=
) 1 (
1 2
) 1 (
2
2
+ ÷
+ ÷
+
÷
z z
z
z

EE452 Digital Control Dr. Salah Foda Page 7

So that F(z) =
) 1 (
5 . 0
2
) 1 (
2
2
2
+ ÷
÷
÷
÷
z z
z z
z
z

Comparing the second term with table entry for cos(neT) (a=0), we find cos(eT)= 1/2,
so that eT = t/3 and
f((nT) = 2(1÷ cos(nt/3)) u(nT)

The following matlab code was used to verify the values of f((nT):

>> delta=[1 zeros(1,19)];
>> num=[0 1 1 0];
>> den=[1 -2 2 -1]);
>> f=filter(num,den,delta);
>> stem(f),grid
>> ylabel('\bf f(nT)'),xlabel('\bf nT')

0 2 4 6 8 10 12 14 16 18 20
0
0.5
1
1.5
2
2.5
3
3.5
4
4.5
5
nT

f
(
n
T
)

Figure 4: Plot of the periodic sequence f(nT).

Useful Hints: The following formulas may be useful and are used quite often
(i)
r
r
N N
n
÷
÷
=
+
=
¯
1
1
r
1
0
n
o o r < 1 (Finite geometric series)
(ii)
r
n
÷
=
¯
·
=
1
r
0
n
o
o r < 1 (Infinite geometric series)
(iii) (a+b)
n
=
¯
=
|
|
.
|

\
|
n
k
k
n
0
a
n÷k
b
k
where
|
|
.
|

\
|
k
n
= n(n÷1)(n÷k+1)/k! (Binomial expansion)
(iv) (a+b)
÷1
= a
÷1
÷ a
÷2
b + a
÷3
b
2
÷ a
÷4
b
3
+ Special case of (iii).
(v) Z{
|
|
.
|

\
|
k
n
o
n-k
}=
1
) (
+
o ÷
k
z
z

EE452 Digital Control Dr. Salah Foda Page 8

Exercises 2:
(1) Find the z-transform for the following functions:
(a) f(t) = u(t÷T)K , t > 0
(b) f(nT) = u(nT)(0.5)
n

(c) f(t) = e
÷3nT
cos(10t nT) u(nT) ( Hint: use the fact that cos(neT) is the real part of e
jneT
)

(d) f(nT) = u(nT)(4)
n+3

(2) Find the initial value f(0) and final value f(·) for the following single sided z-transforms:
(a) F(z) =
1
1 2
÷
÷
z
z

(b) F(z) =
1 2
2
2
+ ÷ z z
z

(c) F(z) =
) 1 (
2
÷ z z
z

(d) F(z) =
) 1 ( ) 1 5 (
2 10
2
2
÷ ÷
+
z z
z z

(3) Find the inverse z-transform for:
(a) F(z) =
T
e z
÷
÷
3

(b) F(z) =
) 2 ( ) 4 4 (
4
2
+ + ÷ z z z
z

(c) F(z) =
) 25 . 0 ( ) 5 . 0 (
3
2
÷ ÷
+
z z
z z

(4) Find the z-transform for the Fibonacci sequence given by the following recursive equation:
x
k+2
= x
k+1
+ x
k
given x
1
= x
0
=1.
i.e. the discrete sequence x
k
= {1, 1, 2, 3, 5, 8, 13, 21, 34, }. Also find the golden ratio t
defined by
· ÷ k
lim x
k+1
/x
k

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->